Alienation and the correctional officer: A multivariate analysis - Walters, Stephen (American journal of criminal justice, 1991)
The increased pressures which have been placed upon correctional institutions in the 1980’s have made the retention of quality correctional officers imperative. Yet many of these officers find prison work to be an unsatisfying experience. This paper attempts to measure levels of alienation among correctional officers and identify factors which may be related to its occurrence. The amount of alienation experienced by 126 correctional officers at a Western state prison was measured utilizing Dean’s Alienation Scale. Alienation levels were found to be related primarily to institutional, and opposed to non-institutional, variables. The implications for correctional administration are discussed.